1983
DOI: 10.1007/bf02372135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 insect growth regulators on larval development, fecundity and egg viability of the coccinelidChilocorus bipustulatus [Col.: Coccinelidae]

Abstract: The effect of 3 insect growth regulators -methoprene, diflubenzuron and RO 13-5223, on the coccinelid Chilocorus bipustulatus L. was studied in the laboratory. Feeding on Chrysomphalus aonidum (L.) or Aspidiotus hederae Vallot (Diaspididae) treated with the IGRs at the concentration of 0.025 % a.i. revealed the following : cliflubenzuron caused a complete mortality of 1St instar larvae ; methoprene and RO 13-5223 did not arrest larval development but inhibited pupation ; fecundity of sexually mature females w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
2

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
1
16
1
2
Order By: Relevance
“…Coccinellidae are apparently more sensitive to insect growth regulators than hymenopteran parasitoids. Peleg (1983a) showed that larvae of C. bipustulatus fed on scales treated with fenoxycarb, methoprene or diflubenzuron did not reach the adult stage. Similar results were obtained in the present study when R. cardinalis fed on I. purchasi was treated with fenoxycarb, buprofezin or pyriproxyfen.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Coccinellidae are apparently more sensitive to insect growth regulators than hymenopteran parasitoids. Peleg (1983a) showed that larvae of C. bipustulatus fed on scales treated with fenoxycarb, methoprene or diflubenzuron did not reach the adult stage. Similar results were obtained in the present study when R. cardinalis fed on I. purchasi was treated with fenoxycarb, buprofezin or pyriproxyfen.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that the products are only slightly harmful to beneficial arthropods, although some moderately adverse effects were recorded when coccinellids were treated with the chemicals. For example, fenoxycarb and methoprene had no adverse effects on the development and activity of several hymenopteran parasitoids of Coccidae and Diaspididae in citrus groves (Peleg, 1983a ;Peleg & Gothilf, 1980) ; however, Abd EI-Kareim et al (1988) showed that Aphytis mytilaspidis (LeBaron) (Hymenoptera : Aphelinidae) was affected by hydroprene, methoprene and kinoprene ; and the juvenoid fenarimol strongly reduced to occurrence of Encarsia berlesei (Howard) (Aphelinidae) (Darvag & Zseller, 1985). Adverse effects of insect growth regulators were recorded on immature stages of several Coccinellidae, i.e., Chilocorus bipustulatus L. (Peleg, 1983a), Stethorus punctilhtm (LeConte) (Hull et aL, 1991), Cryptolaemus montrouzieri Mulsant and Rodolia cardinalis Mulsant (Viggiani & Loia, 1991).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, several studies have recorded longer-term negative effects on ladybirds. These include increased mortality of larvae or inhibition of pupation and egg hatch (Peleg 1983;Smith & Papacek 1990;Mendel et al 1994). Further studies are needed on the longer-term effects of insect growth regulators on adult and larval H. chalybeus.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other IGRs, the eggs and immature stages of predatory beetles, as well as lacewings, can be sensitive to diflubenzuron (Ables et al 1977). However, effects such as reduced egg hatch can be rapidly reversed when the predators enter an untreated environment (Peleg 1983). Diflubenzuron is toxic to crustaceans; however, populations recover rapidly because it rapidly dissipates in water.…”
Section: A Product With Broad Activitymentioning
confidence: 99%